Bone health, activity and sedentariness at age 11-12 years: Cross-sectional Australian population-derived study - Osborn, W; Simm, P; Olds, T; Lycett, K; Mensah, F; Muller, J; Fraysse, F; Ismail, N; Vlok, J; Burgner, D; Carlin, J; Edwards, B; et al. (Elsevier, 2018)
Aim To examine cross-sectional associations of children's bone health (size, density, strength) with moderate-vigorous physical activity (MVPA) and sedentary behaviour by considering: (1) duration of activity, (2) fragmentation, and (3) duration/fragmentation combined. Methods Design: Population-based cross-sectional study. Participants: 11–12 year-olds in the Longitudinal Study of Australian Children's Child Health CheckPoint. Exposures: MVPA and sedentary behaviour (7-day accelerometry), yielding (1) daily average durations (min/day) and (2) fragmentations (the parameter alpha, representing the relationship between activity bout frequency and bout length). Outcomes: Tibial peripheral quantitative computed tomography (bone density, geometry, strength). Analysis: Multivariable regression models including activity durations and fragmentations separately and combined. Results Of 1357 children attending the CheckPoint, 864 (64%) provided both bone and accelerometry data (mean age 11.4 years (standard deviation (SD) 0.5); 49% male). Mean daily MVPA and sedentary behaviour durations were 34.4 min/day (SD 28.3) and 667.9 min/day (SD 71.9) respectively for boys and girls combined. Each additional daily hour of MVPA was associated with small bone health benefits comprising greater periosteal and endosteal circumference (standardised effect sizes 0.25, 95% CI 0.10 to 0.40 and 0.21, 95% CI 0.03 to 0.39, respectively) and bone strength (0.26, 95% CI 0.14 to 0.38). Sedentary duration and fragmentation of either MVPA or sedentary behaviour showed little association with bone health. Conclusions In early adolescence, MVPA duration showed associations with better bone health that, while modest, could be of population-level importance. MVPA fragmentation and sedentary behaviour duration and fragmentation seemed less important.